Federated Electronic Practical Resources using PILAR as VISIR Integrated Tool - Felix, García-Loro (2019)
Practical training is a pillar in technical education. Traditionally, these benefits have been acquired through hands-on laboratory sessions. However, at present, the educational models trend to rely on distance education tools either totally (e-learning, m-learning, etc.) or partially (b-learning). To provide practical training in those educational scenarios is challenging. Remote laboratories --real laboratories, working on real systems and under real conditions, controlled remotely-- can play a fundamental role. Nevertheless, remote laboratories not only provide advantages, but disadvantages of both environments involved in the process: real laboratories and remote communications. Furthermore, remote laboratories add new limitations due to constructive constraints. VISIR (Virtual Instruments System In Reality) is a remote laboratory on top of the state of the art for wiring and measuring electrical and electronics circuits, but VISIR system has his own particular restrictions like any other remote lab. In this context, PILAR (Platform Integration of Laboratories based on the Architecture of visiR) Erasmus Plus project development aims for a federation of five of the existing VISIR nodes in Europe: Blekinge Institute of Technology (BTH), Spanish University for Distance Education (UNED), University of Deusto (UDEUSTO), Carinthia University of Applied Sciences (CUAS), School of Engineering of Polytechnic of Porto (ISEP). This paper describes the benefits that PILAR project will provide to the consortium, and how these physical constraints of the VISIR system can be compensated through the federation, after one year and a half of the project development and having the first draft of the federation and weebsite running.